Problematics of Legal Provisions of Article 31 Paragraph (2) of Government Regulation Number 61 of 2014 Concerning Reproductive Health - Imam Arif Zamani (Yayasan Tranformasi Aksara Digital, 2024)
Abortion due to rape is a complex issue involving legal, moral and religious aspects. The Indonesian government, through Government Regulation No. 61/2014 on Reproductive Health, gives rape victims the right to an abortion within 40 days of the incident. This study aims to analyze the time limit from the perspective of national law and Islamic law and recommend policy improvements. The method used is a theoretical approach with conceptual analysis of national regulations and the views of fuqaha from various madhhabs. The research findings show that the 40-day time limit is considered too short for rape victims, while the 120-day limit in Islamic law is more relevant because it considers fetal development and aspects of justice for victims. In addition, the research found the need for clarity in the mechanism of determining the status of rape victims, which is suggested to involve the Police and the Forensic Medicine Team. As a result of the brief conclusion of this research, it is necessary to recommend revisions to Government Regulation No. 61/2014, especially regarding the abortion grace period and the procedure for determining the status of victims, to ensure justice and legal clarity.